Development Traps and Escaping Development Traps: What Can We Learn from Freedom of Information Laws?. Issue 5 (19th October 2016) - Erlich, Aaron
ABSTRACT: In this talk, I discuss my previous research on the relationship between political competition and the passage of Freedom of Information (FOI) laws. In this previous work, using data on Mexican states, I find that political competition is an important determinant of the speed of passage of FOI laws. I then discuss a larger research project that examines all FOI requests made to the Mexican national government and investigate descriptive statistics related to ProMéxico, Mexico's trade promotion agency. I conclude by arguing that FOI laws should be employed more frequently in the study of international trade.